Elemental, phase and structural analysis of gallstones with hiatal hernias in patients of Kharkiv region - Dikiy, N.P.; Bereznyak, E.P.; Boyko, V.V.; Medvedeva, E.P.; Parhomenko, K.Yu.; Parhomenko, T.A.; Hodyreva, Y.S. (Вопросы атомной науки и техники, 2020)
Gamma activation method on linac NSC KIPT, IR-spectrometry and crystal-optical investigations have been used to determinate the content of elements, the phase analysis and structural features of a different organic and inorganic compound in gallstones of patients with hiatal hernia in Kharkiv region. It is shown that it is possible to establish the presence in gallstones of such compounds as bilirubin and its salts, calcium phosphates, calcium carbonate, and different microelements. In the main, the patients of the Kharkiv region have gallstones of mixed type with a combination of cholesterol, calcium carbonate bilirubinate.